Case report: Targeted treatment strategies for Erdheim-Chester disease - Gulyás, Anita; Pinczés, László Imre; Mátyus, János; Végh, Edit; Bedekovics, Judit; Tóth, Judit; Barna, Sándor; Hunya, Zsolt; Szabó, Imre Lőrinc; Gazdag, Annamária; Illés, Árpád; Magyari, Ferenc (Frontiers in Oncology, 2024)
Introduction: Erdheim-Chester disease (ECD) is a rare disease that belongs to the group of Dendritic and histiocytic neoplasms. Worldwide there are only 2000 cases registered. It can present with a diverse range of symptoms, making differential diagnosis especially difficult. The primary and most important diagnostic tool is biopsy from the affected organ/tissue. Nowadays analysis of different mutations affecting the BRAF and MAPK pathways make it possible to use targeted treatments, such as vemurafenib, dabrafenib or cobimetinib. Objective: Our aim is to present the results of three male patients treated in our hematology department. Results: Our BRAF mutation positive patient presented with retroperitoneal tissue proliferation and diabetes insipidus. The initial therapy of choice was dabrafenib. After 3 months of treatment, 18 F-fluoro-deoxyglucose-positron emission tomography (FDG-PET)/computed tomography (CT) scan showed regression, and after 2 years of treatment no disease activity was detectable. In our second patient a recurrent febrile state (not explained by other reasons) and diabetes insipidus suspected the diagnosis. Femoral bone biopsy confirmed BRAF-negative ECD. First line therapy was interferon alpha. After 3 months of treatment no response was observed on 18 FDG-PET/CT, therefore cobimetinib treatment was started. Control 18 FDG-PET/CT imaging was negative. Our third patient was investigated for dyspnoe, and CT scan showed fibrosis with hilar lymphadenomegaly. Lung biopsy confirmed BRAF negative ECD. We started treatment with interferon alpha, but unfortunately no improvement was detected. Second line cobimetinib treatment resulted in partial metabolic response (PMR) according to control 18 FDG-PET/CT. Conclusion: Our results demonstrate that properly chosen treatment can lead to a good therapeutic response, however dose reduction might be necessary due to side effects. With advanced targeted therapeutic treatment options, survival and quality of life improves significantly.